(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Introduction: Co-management of tuberculosis (TB) and HIV is complicated by pharmacologic drug interactions between rifampicin (RMP) and certain classes of antiretroviral agents. The NNRTIs Nevirapine (NVP) or Efavirenz (EFV), used to HIV infection, are known to induce the CYP 450 enzyme system. Thus when RMP is co-administered along with NVP or EFV, the bioavailability of RMP could be lowered leading to drug resistance and treatment failure. Objectives: To study the steady state pharmacokinetics of RMP in HIV and HIV-TB patients receiving antiretroviral regimens containing NVP or EFV respectively. Methods: The study population comprised of HIV and HIV-TB patients undergoing antiretroviral treatment with NVP and EFV containing regimens respectively. These patients were also receiving concomitant RMP. Rifampicin was estimated by HPLC in blood collected at different time points after drug administration. The pharmacokinetic variables of RMP were calculated using WinNonlin software. Results & Conclusions: Co-administration of NVP or EFV did not alter the pharmacokinetics of RMP in HIV and HIV-TB patients, suggesting that the dose of RMP need not be altered during antiretroviral treatment with NVP or EFV. Key words: Rifampicin; nevirapine; efavirenz; drug-drug interactions; HIV-TB DOI: 10.3126/saarctb.v5i2.3068 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 1-5